The Effect of User-Generated Content, Discount Promotions, and Reviews on Impulsive Buying Among Gen Z on Tiktok Shop - U. Ulfamiyati; Jaya Ramadaey Bangsa (Manunggal Halim Jaya, 2026)
The development of social commerce through TikTok Shop has changed consumer shopping behavior, especially among male Gen Z consumers, known as digital natives. The integration of visual content, social interaction, and ease of transactions has led to increased impulsive buying. This study aims to analyze the influence of user-generated content, discount promotions, and reviews on impulsive buying among male Gen Z consumers on TikTok Shop. This study uses a quantitative, correlational method. The sample of this study was 110 male Gen Z respondents aged 13-28 years who reside in Temanggung Regency and have made a purchase on TikTok Shop at least once in the last six months. The sampling technique used was purposive sampling, and data were collected through an online questionnaire. Data analysis used Partial Least Squares-Structural Equation Modeling (PLS-SEM) with the help of SmartPLS 3.0. The results showed that user-generated content has a positive and significant effect on impulsive buying (p-value <), indicating that authentic user-generated content is more attractive and trustworthy. Discount promotions have a positive and significant effect on impulsive buying (p-value <), suggesting that price offers and time limits can encourage impulsive buying. Reviews also have a positive and significant effect on impulsive buying (p-value <), indicating the importance of social validation in the decision-making process. Simultaneously, all three independent variables contribute significantly to impulsive buying among Gen Z males on TikTok Shop.